"You have to do something beyond containing": developing inclusive systems in a partnership of primary schools. Issue 3 (3rd July 2018) - Rose, Jo; Stanforth, Alex; Gilmore, Gwen; Bevan-Brown, Jill
ABSTRACT: Reducing fixed term exclusions (FTE) in primary schools is a difficult proposition. This research discusses how a partnership of primary schools developed more inclusive systems to support students previously given FTEs for disciplinary purposes. Longitudinal data from interviews and documentary sources trace the development of an approach amongst primary schools with previously high levels of FTE. The process of developing a model of transferred inclusion (TI) within the partnership led to schools changing practices around behaviour management, thus developing more inclusive systems. The paper elaborates on partnership work around the TI project that opened up discussion and questioning of practice around behaviour, leading to schools thinking about their systemic practice. The benefits of TI, therefore, were a prompt for development, rather than just an intervention to reduce exclusions. Changes in practice supported through the TI process lead to claims that substantive change would not have happened without the TI project.